Strengthening Islamic Education to Preschool Students in Jepara, Indonesia (THUFULA, 2022)
Abstract: This research describes about strengthening Islamic education to preschooler in Jepara district. This study is field-research, the premier data I data which obtained from research field. The approach is qualitative. Technique of data collection in this research is data from research field where reality will be investigated. The steps are: interview, observation, and documentation. The technique of data analysis in this research is in accordance with statement by Miles and Huberman which are data reduction, data display, and data verification. The results of research are: first, base and purposes of Islamic education as strong reference is Qur’an, as in QS. Luqman: 13-19. While the purposes of Islamic education stated in QS. Ali Imran: 102. Second, curriculum those become foundation of strengthening Islamic education to early childhood education students are reflected in core competence and basic competences like religious, social, science, and skill. Third, relevant method in strengthening Islamic education to early childhood education students is play while learning, story-telling, singing, giving model, habituate, and study tour. Fourth, assessment or evaluation is done through observation, anecdote, dialogue, homework, creation, and portfolio.Keywords: Islamic Education, Early Childhood Education, Students